ANALISIS PENGARUH DIMENSI KUALITAS LAYANAN, CORPORATE IMAGE TERHADAP KEPUASAN MAHASISWA DI UNIVERSITAS PATTIMURA (UNPATTI) AMBON - Khaeril dan; Dessy Balik (IAIN Ambon, 2017)
This research aims to determine (1) whether the service quality dimensions has significant and positive effect on the students satisfaction of Pattimura University Ambon?; (2) whether the corporate image has significant and positive effect on the student satisfaction of Pattimura University, Ambon? This research is descriptive using expalanatory methods, data collection is taken through observation, interviews and documentation. Data are analyzed with SPSS version 17.0, through multiple linear regression analysis. The results showed that there are three positive and significant variables which has effect on the student satisfaction of the Pattimura University, Ambon is Empathy (X4), Reability (X5), and Corporate image (X6). There are also 3 insignificant variables to the students satisfaction in the campus of Unpatti Ambon i.e.: responsivness (X1), Assurance (X2), and Tanggible (X3). The most dominant influence variable on the student satisfaction in the campus of Unpatti Ambon is empathy variable (X4) with coefisien of 23.1%, followed by Reability variable with research coefisien at 19.5%, and corporate image (X6) with research coefficient of 17, 3%. Key words: Responsiveness, Assurance, Tanggible, Empathy, Reability, Corporate Image, Student Satisfaction